Dinamika Profitabilitas dan Kebijakan Hutang: Dampaknya terhadap Evaluasi Nilai Perusahaan melalui Kebijakan Dividen - Ramadhan, Amanda (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2024)
In a dynamic business environment, companies are faced with the challenge of maximizing company value. Profitability and debt policy have been identified as key factors influencing company valuation. This research aims to understand the complex relationship between profitability and debt policy, and analyze how the interaction of these two factors influences the assessment of company value through the influence of dividend policy. This research method involves careful statistical analysis of the relevant company's financial data. Time series data will be taken from financial reports for a certain period, and a regression model will be used to measure the correlation between profitability, debt policy, and company value assessment through studying dividend policy. It is hoped that the results of this research will provide an in-depth understanding of how the dynamics of profitability and debt policy influence each other in the context of assessing company value. In addition, this research will provide insight into the crucial role of dividend policy in articulating the impact of these two factors.